INTERNALISASI NILAI-NILAI AGAMA ISLAM DALAM MENUMBUHKAN MODERASI BERAGAMA DI SMAN 1 SLEMAN - Ihsan, Achmad Yusril; Amalia, Nasywa (Universitas Nahdlatul Ulama Al Ghazali Cilacap, 2022)
Indonesia is a diverse country. Of course, with the variety of Indonesian society, it has become a must to maintain diversity and pluralism as a form of tolerance between fellow Indonesian citizens. The key to creating tolerance and harmony between people is to respect each other's rights as citizens, including in carrying out religious sharia that is believed by every citizen. The purpose of this study is to analyze the process of internalization of Islamic religious values and strategies in applying religious moderation in the world of education and its influence on Islamic religious education. This type of research is qualitative research with the approach used in this study is phenomenology. Data collection techniques are carried out through observation, interviews, and documentation. The results of this study show the school's strategy in strengthening the values of Islamic religious education for Muslim students in fostering an attitude of religious moderation. Internalization is designed through learning, development, extracurricular, cocurricular, and daily habituation. The reality of diversity in SMAN 1 Sleman shows an attitude of mutual acceptance of differences, mutual respect, and having the same right to practice the sharia of each religion.